The nature and function of intuitive thought and decision making - Jarvilehto, Lauri (SpringerBriefs in Well-Being and Quality of Life Research, 2015)
This book focuses on the very nature and function of intuitive thought. It presents an up-to-date scientific model on how the non-conscious and intuitive thought processes work in human beings. The model is based on mainstream theorizing on intuition, as well as qualitative meta-analysis of the empirical data available in the research literature. It combines recent work in the fields of philosophy of mind, cognitive psychology and positive psychology. While systematic research in intuition is relatively new, there is an abundance of positions advocating more or less imaginative ideas of what intuition is about, ranging from quantum mechanical phenomena to new age ideologies. Research in the past few decades, in particular by proponents of the dual processing theory of thought such as Daniel Kahneman and Jonathan Evans, offers powerful tools to address and evaluate the question of intuition without the need to resort to spiritual entities. Within the framework of the dual processing theory, backed up by findings in positive psychology, intuition turns out to be the capacity to carry out complex cognitive operations within a specific domain of operations familiar to the agent.